2018
DOI: 10.1007/s10803-018-3771-y
|View full text |Cite
|
Sign up to set email alerts
|

Interrupted Time Experience in Autism Spectrum Disorder: Empirical Evidence from Content Analysis

Abstract: Although the experience of time is of central relevance for psychopathology, qualitative approaches to study the inner experience of time have been largely neglected in autism research. We present results from qualitative data acquired from 26 adults with high functioning autism spectrum disorder (ASD). Employing inductive content analysis we identified a distinct pattern of interrupted time experience in ASD. Individuals with ASD seemed to implement structured and routine behavior by future planning to guaran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 68 publications
(105 reference statements)
1
27
0
Order By: Relevance
“…ASD has also been associated with atypical time processing. Interviews have shown that individuals with ASD tend to rely on routines and repetitive behaviours to help the structuring of their subjective time experience [98,99]. Moreover, empirical findings found that individuals with ASD tend to perceive time atypically ranging from impaired interval timing to intact or increased temporal event structure coding and that this correlates with nonverbal communication difficulty (e.g.…”
Section: Dyads With Autistic Participants Show Reduced Ipsmentioning
confidence: 99%
“…ASD has also been associated with atypical time processing. Interviews have shown that individuals with ASD tend to rely on routines and repetitive behaviours to help the structuring of their subjective time experience [98,99]. Moreover, empirical findings found that individuals with ASD tend to perceive time atypically ranging from impaired interval timing to intact or increased temporal event structure coding and that this correlates with nonverbal communication difficulty (e.g.…”
Section: Dyads With Autistic Participants Show Reduced Ipsmentioning
confidence: 99%
“…Yet, the assessment is not straightforward or standardized so far and is hampered by the fact that non-verbal behavior is not necessarily reduced in ASD, but abnormal in the quality of its temporal coordination with own verbal output (de Marchena and Eigsti, 2010) and that of an interaction partner. Literature provides evidence for aberrations in temporal processing (Allman and Falter, 2015) and time experience in ASD (Vogel et al, 2019), potentially affecting nonverbal communication. In fact, findings have shown that ASD can be characterized by increased temporal resolution associated with the severity of (non-verbal) communication impairments in ASD (Falter et al, 2012(Falter et al, , 2013Menassa et al, 2018; but see Isaksson et al, 2018).…”
Section: Whole-body Movements As a Feature In ML Algorithms In Asdmentioning
confidence: 99%
“…For patients with schizophrenia, disturbances in temporal processing have repeatedly been implicated ( Fuchs, 2007 ; Vogeley and Kupke, 2007 ; Fletcher and Frith, 2009 ; Vogel D. et al, 2019 ). It has been proposed that a disruption or fragmentation in temporal continuity may lie at the heart of explaining psychotic symptoms.…”
Section: Enduring Situated Cognition and Psychopathologymentioning
confidence: 99%
“…From a phenomenological point of view, it has primarily been argued that this fragmentation is due to an alteration of the future directed protention on the microlayer of time ( Kupke, 2009 , pp. 53–62; Fuchs, 2013 ; Stanghellini et al, 2016 ; Vogel D. H. V. et al, 2019 ; Vogel D. et al, 2019 ). In this context, protention is understood as analogous to an anticipatory process ( Fuchs, 2013 ), which graduates future perceptions along a spectrum of probability.…”
Section: Enduring Situated Cognition and Psychopathologymentioning
confidence: 99%
See 1 more Smart Citation